Semiempirical Model for Ionospheric Absorption based on the NRLMSISE‐00 atmospheric model. Issue 2 (5th February 2014) - Pederick, L. H.; Cervera, M. A.
<x xml:space="preserve">Abstract</x> The strength of high‐frequency radio signals, when refracted by the ionosphere, can be strongly influenced by ionospheric absorption. Accurate modeling of the amount of this absorption is a vital part of many studies of radio waves propagating in the ionosphere. We have developed a new, flexible model of ionospheric absorption, the Semiempirical Model for Ionospheric Absorption based on the NRLMSISE‐00 atmospheric model (SiMIAN). This article describes the methods and formulae used by SiMIAN, a comparison of SiMIAN with an older absorption model, and validation work performed by simulating the power returned in vertical incidence soundings of the ionosphere and comparing the results with real soundings.